2021
DOI: 10.3390/cells10113264
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Killed Lactobacilli Preparations Promote Healing in the Experimental Cutaneous Wounds

Abstract: Probiotics are defined as microorganisms with beneficial health effects when consumed by humans, being applied mainly to improve allergic or intestinal diseases. Due to the increasing resistance of pathogens to antibiotics, the abuse of antibiotics becomes inefficient in the skin and in systemic infections, and probiotics may also provide the protective effect for repairing the healing of infected cutaneous wounds. Here we selected two Lactobacillus strains, L. plantarum GMNL-6 and L. paracasei GMNL-653, in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Kanmani et al showed that LAB strains (Lactiplantibacillus plantarum, Lactobacillus brevis, and Weissella cibaria) attenuated hepatic stellate cell (HSC) activation mediated by the profibrotic cytokine TGF-β, thereby preventing liver fibrosis. Tsai et al demonstrated that treatment with heat-killed probiotics (L. plantarum GMNL-6 and Lactobacillus paracasei GMNL-653) significantly inhibited the expression of α-SMA and Smad2/3, thus promoting wound healing of mouse tail skin without excessive scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…Kanmani et al showed that LAB strains (Lactiplantibacillus plantarum, Lactobacillus brevis, and Weissella cibaria) attenuated hepatic stellate cell (HSC) activation mediated by the profibrotic cytokine TGF-β, thereby preventing liver fibrosis. Tsai et al demonstrated that treatment with heat-killed probiotics (L. plantarum GMNL-6 and Lactobacillus paracasei GMNL-653) significantly inhibited the expression of α-SMA and Smad2/3, thus promoting wound healing of mouse tail skin without excessive scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…Topical cream containing heat-killed L. platarum GMNL-6 also improves human skin health [ 23 ]. We previously demonstrated that the treatment of smeared gel containing heat-killed L. platarum GMNL-6 and L. paracasei GMNL-653 on wounded mouse tails exhibited excellent healing ability and the capacity to prevent excessive fibrosis through the suppression of TGF-β/pSmad signaling in the skin wound repair [ 22 ]. In the current study, we found that heat-killed L. paracasei GMNL-653 could ameliorate damaged human scalp health for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…The glycolipopeptide of Lactiplantibacillus pentosus and Lacticaseibacillus paracasei has anti-adhesion and anti-microbial activity against pathogen in the skin microflora [ 21 ]. Our previous studies demonstrated that heat-killed Lactobacilli preparations from L. plantarum GMNL-6 and L. paracasei GMNL-653 promote skin wound healing and preventing excessive fibrosis by suppressing TGF-β/pSmad signaling [ 22 ]. Lipoteichoic acid, the major cell wall component of GMNL-6, has a beneficial effect on skin care [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was shown that probiotic supplementation with either Lactobacillus paracasei, B. lactis, Lactobacillus rhamnosus, L. acidophilus , or with Lactobacillus rhamnosus , Bifidobacterium longum can accelerate trauma healing after surgeries, with better results when simultaneously using multiple strains [ 76 , 77 , 78 ]. The re-epithelialization in DSS-induced mice was also faster after treatment with Bifidobacterium bifidum , L. acidophilus and Bacillus amyloliquefaciens [ 79 ] In a study by Tsai et al, the co-administration of heat-killed L. plantarum and Lactobacillus paracasei promoted healing in mice [ 80 ], while Kazemi et al showed that the extracts of L. plantarum and Lactobacillus casei promoted the proliferation of mesenchymal stem cells [ 81 ]. Furthermore, a four-strain supplement containing L. acidophilus, L. plantarum, Lactobacillus rhamnosus and Enterococcus faecium benefited epithelial tight junction integrity and promoted wound healing [ 82 ], and another one containing L. acidophilus, L. plantarum, B. lactis and Bifidobacterium breve can strengthen the epithelial barrier of the gut [ 83 ].…”
Section: Discussionmentioning
confidence: 99%